2016
DOI: 10.5271/sjweh.3573
|View full text |Cite
|
Sign up to set email alerts
|

Internet- and mobile-based stress management for employees with adherence-focused guidance: efficacy and mechanism of change

Abstract: The present study adds to the literature by showing that (1) a newly developed internet-based stress-management intervention based on Lazarus' transactional stress model can be effective with only limited human support (<1 hour per participant), and (2) cognitive behavioral therapy (CBT)-based interventions can have enduring effects on mental health and work-related health outcomes that go beyond immediate short-term effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
104
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 109 publications
(111 citation statements)
references
References 48 publications
6
104
0
Order By: Relevance
“…In the present study, all patients had moderate to severe pre-treatment symptoms, as is expected in a clinical sample. Comparing our results to other studies of ICBT where participants had elevated levels of stress or were diagnosed with stress-related disorders [10][11][12], effects on mental health outcomes were generally equivalent. The only exception was the effect on disturbed sleep, which was larger in our study (d = 1.05 as compared to d = 0.34-0.52).…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…In the present study, all patients had moderate to severe pre-treatment symptoms, as is expected in a clinical sample. Comparing our results to other studies of ICBT where participants had elevated levels of stress or were diagnosed with stress-related disorders [10][11][12], effects on mental health outcomes were generally equivalent. The only exception was the effect on disturbed sleep, which was larger in our study (d = 1.05 as compared to d = 0.34-0.52).…”
Section: Discussionsupporting
confidence: 58%
“…It is possible that the early interventions targeting increased recovery and disturbed sleep in the present study (weeks 2 and 3 of treatment) had positive effects on sleep. Previous studies have included optional interventions for improved sleep, generally later in the treatment course [10][11][12]. Studies are needed to investigate potential mediators of change in ICBT for symptoms of chronic stress, particularly the mediating effect of sleep in improving stress-related outcomes in CBT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For nine studies, only posttest assessments were available. The participants received guidance in seven studies [24,26,27,34,35,37,42], one study [32] assessed a less intensive guidance format (adherence-focused guidance: combination of reminders and written feedback only on request of the participants), and 16 studies (18 comparisons) investigated unguided interventions. Nine unguided studies reported the use of automated or telephone and mail reminders for completion of the intervention [23,25,28,29,33,36,42,55,56] (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…In most cases, the concealment of allocation was insufficiently described, and only 13 of 23 studies reported adequate handling of missing data. In particular, the risk for selective outcome reporting was unclear because the study registration prior to the trials could only be retrieved from three studies [31,32,34]. Although another four studies registered their trial [28,30,33,36], this step occurred retrospectively.…”
Section: Resultsmentioning
confidence: 99%